2013
DOI: 10.1371/journal.pcbi.1003057
|View full text |Cite
|
Sign up to set email alerts
|

Two Misfolding Routes for the Prion Protein around pH 4.5

Abstract: Using molecular dynamics simulations, we show that the prion protein (PrP) exhibits a dual behavior, with two possible transition routes, upon protonation of H187 around pH 4.5, which mimics specific conditions encountered in endosomes. Our results suggest a picture in which the protonated imidazole ring of H187 experiences an electrostatic repulsion with the nearby guanidinium group of R136, to which the system responds by pushing either H187 or R136 sidechains away from their native cavities. The regions to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 66 publications
2
19
0
Order By: Relevance
“…Already in E. coli, the expressed DelT 221 protein was routed into inclusion bodies, a phenomenon that was previously reported in relation to the expression of misfolded proteins by Kraft et al 2010 [31] and by Gerrec et al 2013 [32]. It appears that the bacteria “conceived” the truncated protein variant as “junk” and therefore removed it by routing it into the inclusion bodies.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Already in E. coli, the expressed DelT 221 protein was routed into inclusion bodies, a phenomenon that was previously reported in relation to the expression of misfolded proteins by Kraft et al 2010 [31] and by Gerrec et al 2013 [32]. It appears that the bacteria “conceived” the truncated protein variant as “junk” and therefore removed it by routing it into the inclusion bodies.…”
Section: Discussionmentioning
confidence: 77%
“…High concentrations of urea were used to refold the protein in bacteria, and recover it out of the inclusion bodies to enable its purification. It remains to be seen what the degradation process of the mutated protein is in human placenta and how to gain its recovery in human with a potential procedure for pH changes [32] or the formation of multi-vascular bodies as described by Wang et al 2011 [33] . At present we assume that the cytoplasm recognized the misfolded mutated DelT 221 at a “control checkpoint” already at the endoplasmic reticulum or the Golgi and routes it for a fast turnover to avoid potential toxic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Garrec et al (2013) reported that the salt linkage of HIS187 and ARG136 of mouse PrP causes "two misfolding routes for the prion protein" (Garrec et al (2013)). For RaPrP C , we found that at HIS187 the salt bridge HIS186-ARG155 contributes to the structural stability (Table 1).…”
Section: Kmentioning
confidence: 99%
“…At low pH, physiological amounts of salt trigger PrP misfolding and oligomerization. Computational studies have shown that movement of β1‐α1‐β2 away from the rest of the CTD and breakage of long‐range salt bridges is an important step that precedes misfolding of PrP 15,61,62 . These observations are corroborated by biophysical studies 29 .…”
Section: Discussionmentioning
confidence: 79%